Квантові точки та їх застосування у медичній візуалізації - Чубукін, О. С.; Зубенко, O. О. (ХНУРЕ, 2025)
Quantum dots (QDs), are nanocrystals with unique optical and electronic properties that can be tuned to make them ideal for medical imaging. They are used in imaging techniques such as fluorescence imaging and magnetic resonance imaging (MRI), where their magnetic properties improve image contrast. In addition, CT scanners can be used in positron emission tomography (PET), which provides highly sensitive data on biological processes. One of the biggest advantages of CT scans is their multifunctionality, which allows for simultaneous diagnosis and treatment, which is the basis of theranostics. This approach reduces treatment costs and increases its effectiveness.
Keywords: квантові точки; медична візуалізація